CO2 foam concrete material based on solid waste-based multi-component gel system and preparation method
By using the use of carbon dioxide foam concrete materials and the use of solid waste -based diverse gel system and CO2 reaction technology, the existing materials are difficult to take into account the problem of light quality and high intensity, and the comprehensive performance improvement of light quality, high -strength and insulation is achieved.
Patent Information
- Application Number
- CN202411461256.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing carbon dioxide foam concrete materials are difficult to take into account the requirements of lightweight and high strength under high water-cement ratio and high carbon dioxide concentration, and have failed to fully utilize the reaction between CO2 and the gelling system to strengthen their performance.
The CO2 foam concrete material based on the solid waste -based diverse gel system is used to premature and complex the solid waste -based sulfur sulfurite cement, semi -water gypsum, silicate cement and other components. Auxiliary materials such as doses and calcium calcium, combined with the reaction between CO2 and aluminum sulfate, form a lightweight and high -strength foam concrete.
On the basis of ensuring the strength requirements, the apparent density of foam concrete is significantly reduced, its mechanical properties are improved, and the requirements of light quality, high strength and insulation are met.
Smart Images

Figure CN119330674A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of green low-zero carbon building materials, and specifically relates to a solid waste-based carbon dioxide foam concrete and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] At present, in the preparation of carbon dioxide foam concrete materials, the cementitious materials are generally based on silicate cement and sulphoaluminate cement, and mineral admixtures such as fly ash, mineral powder, and carbide slag are added. Carbon dioxide is introduced by physical or chemical methods and prepared at a high water-cement ratio. Carbon dioxide foam concrete materials mainly focus on parameters such as density, compressive strength, thermal conductivity, porosity, and water absorption. However, under conventional preparation processes, carbon dioxide foam concrete materials have problems such as high density and low compressive strength. The density of foam concrete materials is positively correlated with the compressive strength, and a decrease in density is bound to lead to a decrease in compressive strength. Therefore, the realization of high compressive strength still needs to take into account the requirements of low density and lightweight. For foam concrete materials, light weight, low density, and high compressive strength are both beneficial to it. Although CO2 foam concrete increases the porosity and carbonization rate under high water-cement ratio and high carbon dioxide concentration, it is difficult to take into account the requirements of light weight and high strength.
[0004] Therefore, the paper "Functional Ternary Cementitious Material Mix Design and Performance Research" discloses a ternary cementitious material based on sulphoaluminate cement-Portland cement-semi-hydrated gypsum, but does not consider the reaction of CO2 with the cementitious system and further enhance its positive effect on the performance of foamed concrete, and cannot meet the demand for lighter foamed concrete materials and achieve the goal of rapid solidification and stable foaming. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a CO2 foam concrete material based on a solid waste-based multi-component gelling system and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] For the following questions:
[0008] 1. The various admixture minerals used in existing carbon dioxide foam concrete materials emphasize improving strength while ignoring the design goal of lightweight;
[0009] 2. The enhancement of the performance of foamed concrete by the reaction of CO2 and the cementitious system is not considered.
[0010] 3. Under high water-cement ratio, the strength of carbon dioxide foam concrete material is difficult to meet industrial requirements;
[0011] 4. Under high carbon dioxide concentration, it is difficult to achieve rapid solidification of carbon dioxide foam.
[0012] The first aspect of the present invention provides a CO2 foam concrete material based on a solid waste-based multi-component cementitious system, which is composed of the following components in percentage by mass: 20%-42% of solid waste-based sulphoaluminate cement, 15%-60% of hemihydrate gypsum, 6%-15% of Portland cement, 0-20% of mineral powder, 2%-4% of sodium bicarbonate, 3%-6% of potassium aluminum sulfate, 0.2%-0.4% of retarder, 0.02%-0.2% of water reducer, and 0.02%-0.06% of calcium stearate, and the sum of the percentages of each raw material is 100%.
[0013] In some embodiments, the preparation method of the solid waste-based sulphoaluminate cement comprises: drying and mixing 80-90 parts of sulphoaluminate cement clinker, 15-20 parts of desulfurized gypsum, and 5-10 parts of stone powder; adding the mixed raw materials into a kiln and calcining them at a temperature of 1250-1300°C for 30-40 minutes to prepare solid waste-based sulphoaluminate cement.
[0014] In some embodiments, the retarder is at least one of boric acid and tartaric acid.
[0015] In some embodiments, the water reducer is at least one of a polycarboxylate water reducer and a naphthalene-based water reducer.
[0016] In some embodiments, the water-cement ratio is 0.3-0.45.
[0017] The second aspect of the present invention provides a method for preparing a CO2 foam concrete material based on a solid waste-based multi-component gelling system, comprising:
[0018] The solid waste-based sulphoaluminate cement, hemihydrate gypsum, silicate cement, mineral powder and sodium bicarbonate are uniformly mixed to obtain a premix;
[0019] Adding a retarder, a water reducing agent and calcium stearate to the premix, and mixing them evenly to obtain a composite material;
[0020] Prepare potassium aluminum sulfate solution;
[0021] Adding the potassium aluminum sulfate solution to the composite material, mixing evenly, to obtain a slurry;
[0022] The slurry is poured into a mold, allowed to grow and form, demoulded, and cured to obtain the product.
[0023] In some embodiments, a retarder, a water reducing agent, and calcium stearate are added to the premix and mixed for 2-5 minutes.
[0024] In some embodiments, in the potassium aluminum sulfate solution, the mass ratio of potassium aluminum sulfate to water is 3-6:30-45.
[0025] In some embodiments, the potassium aluminum sulfate solution is added to the composite material and mixed for 120-180 seconds.
[0026] More specifically, they include:
[0027] The following steps are involved:
[0028] (1) 20-42 parts of solid waste-based sulphoaluminate cement, 15-60 parts of hemihydrate gypsum, 6-15 parts of Portland cement, 0-20 parts of mineral powder, and 2-4 parts of sodium bicarbonate are fully premixed and stirred for use;
[0029] (2) The raw material prepared in (1) is further mixed with 0.2-0.4 parts of a retarder, 0.02-0.2 parts of a water reducing agent, and 0.02-0.06 parts of calcium stearate, and the mixture is further mixed for 2 minutes to prepare a composite material for use;
[0030] (3) Take 30-45 parts of tap water, add 3-6 parts of potassium aluminum sulfate, and stir rapidly for 30-60 seconds to prepare a mixed solution for later use;
[0031] (4) Pour the mixed solution in (3) into the solution in (2) at once and stir rapidly for 120-180 seconds;
[0032] (5) The slurry mixed in (4) is poured into a mold, and allowed to stand for 1-2 days, and then demolded and cured under standard curing conditions to obtain a lightweight and high-strength carbon dioxide foam concrete material.
[0033] The third aspect of the present invention provides the application of the above-mentioned CO2 foam concrete material based on the solid waste-based multi-component gelling system in the fields of construction and road construction.
[0034] It can be seen that the present invention effectively solves the following problems:
[0035] (1) Preparation of lightweight carbon dioxide foam concrete;
[0036] (2) Consider using CO2 to react with the cementitious system to enhance the performance of foamed concrete;
[0037] (3) The compound materials meet the high strength requirements of foam concrete;
[0038] (4) The pores of carbon dioxide foam concrete are optimized at low water-cement ratio.
[0039] Beneficial Effects of the Invention
[0040] (1) The present invention significantly reduces the apparent density while ensuring that the foam concrete meets the strength requirements;
[0041] (2) The composite system formed by the solid waste-based sulphoaluminate cement, silicate cement and hemihydrate gypsum of the present invention significantly improves the mechanical properties of carbon dioxide foam concrete;
[0042] (3) The solid waste-based CO2 foamed concrete and its preparation process of the present invention fully meet the requirements of lightweight, high strength and thermal insulation of foamed concrete;
[0043] (4) The hydration synergistic effect of the sulphoaluminate cement, silicate cement and hemihydrate gypsum of the present invention greatly improves the mechanical properties and other parameters of the carbon dioxide foam concrete material, which provides a basis for lightweight and high-strength design.
[0044] (5) The carbon dioxide of the present invention has a positive effect on the system formed by sulphoaluminate cement, silicate cement and hemihydrate gypsum.
[0045] (6) The present invention can meet the construction requirements of prefabricated buildings after maintenance. While reducing the density, the strength can still meet the standard limit and the maintenance period is short. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0047] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0048] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0049] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0050] In the following embodiments, the preparation method of the solid waste-based sulphoaluminate cement includes: drying and mixing 80 parts of sulphoaluminate cement clinker, 15 parts of desulfurized gypsum, and 5 parts of stone powder; adding the mixed raw materials into a kiln and calcining them at a temperature of 1250° C. for 30 minutes to prepare solid waste-based sulphoaluminate cement.
[0051] The retarder is boric acid.
[0052] The water reducer is a commercially available polycarboxylate water reducer.
[0053] The materials used in the comparative experiment are as follows: 36 parts of desulfurized gypsum, 16 parts of red mud, 22 parts of aluminum ash, and 26 parts of calcium carbide slag. Preparation method: Physical foaming of air, prefabricated foam and slurry are mixed to prepare foamed concrete, and the test results are shown in the "Comparative Results".
[0054] Example 1
[0055] A solid waste-based CO2 foam concrete and a preparation process thereof, wherein the carbon dioxide foam concrete is composed of solid waste-based sulfoaluminate cement, silicate cement, semi-hydrated gypsum, and mineral powder as a matrix cementitious mixture, a retarder, a water reducer, and a foam stabilizer as auxiliary materials, sodium bicarbonate and potassium aluminum sulfate as foaming agents, the cementitious materials are fully mixed and the auxiliary materials and an appropriate amount of sodium bicarbonate are added, and an appropriate amount of potassium aluminum sulfate is added to a certain amount of water to dissolve and stir at high speed, the formed solution is added to the fully mixed cementitious materials at one time, and quickly stirred together, and finally poured, quickly formed, and standardly cured to obtain the concrete. The raw materials for preparing the solid waste-based sulfoaluminate cement are: desulfurized gypsum, aluminum ash, steel slag, carbide slag, and limestone tailings, which are all bulk industrial solid wastes. The water reducer is a polycarboxylate water reducer, and the foam stabilizer is calcium stearate, and the water meets the requirements for concrete mixing water.
[0056] A solid waste-based CO2 foam concrete and a preparation process thereof proposed in the present invention include the following steps:
[0057] (1) 20 parts of solid waste-based sulphoaluminate cement, 50 parts of hemihydrate gypsum, 10 parts of Portland cement, 20 parts of mineral powder and 2 parts of sodium bicarbonate are fully premixed and stirred for use;
[0058] (2) The raw material prepared in (1) is further mixed with 0.2 parts of retarder, 0.02 parts of water reducing agent, and 0.04 parts of calcium stearate, and the mixture is further mixed for 2 minutes to prepare a composite material for use;
[0059] (3) Take 30% tap water, add 3% potassium aluminum sulfate, and stir rapidly for 30-60 seconds to prepare a mixed solution for later use;
[0060] (4) Pour the mixed solution in (3) into the solution in (2) at once and stir rapidly for 120-180 seconds;
[0061] (5) The slurry mixed in (4) is poured into a mold, and allowed to stand for 1-2 days, and then demolded and cured under standard curing conditions to obtain a lightweight and high-strength carbon dioxide foam concrete material.
[0062] Table 1 Performance of carbon dioxide foam concrete in Example 1
[0063]
[0064]
[0065] Example 2
[0066] A solid waste-based CO2 foam concrete and a preparation process thereof, wherein the carbon dioxide foam concrete is composed of solid waste-based sulfoaluminate cement, silicate cement, semi-hydrated gypsum, silica fume, and mineral powder as a matrix cementitious mixture, a retarder, a water reducer, a gypsum retarder, and a foam stabilizer as auxiliary materials, sodium bicarbonate and potassium aluminum sulfate as foaming agents, the cementitious materials are fully mixed and the auxiliary materials and an appropriate amount of sodium bicarbonate are added, and an appropriate amount of potassium aluminum sulfate is added to a certain amount of water to dissolve and stir at high speed, and the formed solution is added to the fully mixed cementitious materials at one time, and quickly stirred together, and finally poured, quickly formed, and standardly cured to obtain the concrete. The raw materials for preparing the solid waste-based sulfoaluminate cement are: desulfurized gypsum, aluminum ash, steel slag, carbide slag, and limestone tailings, which are all bulk industrial solid wastes. The water reducer is a polycarboxylate water reducer, and the foam stabilizer is calcium stearate, and the water meets the requirements for concrete mixing water.
[0067] A solid waste-based CO2 foam concrete and a preparation process thereof proposed in the present invention include the following steps:
[0068] (1) 20 parts of solid waste-based sulphoaluminate cement, 50 parts of hemihydrate gypsum, 10 parts of silicate cement, 20 parts of mineral powder and 4 parts of sodium bicarbonate are fully premixed and stirred for use;
[0069] (2) The raw material prepared in (1) is further mixed with 0.2 parts of retarder, 0.02 parts of water reducing agent, and 0.06 parts of calcium stearate, and the mixture is further mixed for 2 minutes to prepare a composite material for use;
[0070] (3) Take 45% tap water, add 6% potassium aluminum sulfate, and stir rapidly for 60 seconds to make a mixed solution for later use;
[0071] (4) Pour the mixed solution in (3) into the solution in (2) at once and stir rapidly for 180 seconds;
[0072] (5) The slurry mixed in (4) is poured into a mold, allowed to stand for 2 days, demolded, and cured under standard curing conditions to obtain a lightweight and high-strength carbon dioxide foam concrete material.
[0073] Table 2 Performance of carbon dioxide foam concrete in implementation case 2
[0074]
[0075] Example 3
[0076] A solid waste-based CO2 foam concrete and a preparation process thereof, wherein the carbon dioxide foam concrete is composed of solid waste-based sulfoaluminate cement, silicate cement, semi-hydrated gypsum, silica fume, and mineral powder as a matrix cementitious mixture, a retarder, a water reducer, a gypsum retarder, and a foam stabilizer as auxiliary materials, sodium bicarbonate and potassium aluminum sulfate as foaming agents, the cementitious materials are fully mixed and the auxiliary materials and an appropriate amount of sodium bicarbonate are added, and an appropriate amount of potassium aluminum sulfate is added to a certain amount of water to dissolve and stir at high speed, and the formed solution is added to the fully mixed cementitious materials at one time, and quickly stirred together, and finally poured, quickly formed, and standardly cured to obtain the concrete. The raw materials for preparing the solid waste-based sulfoaluminate cement are: desulfurized gypsum, aluminum ash, steel slag, carbide slag, and limestone tailings, which are all bulk industrial solid wastes. The water reducer is a polycarboxylate water reducer, and the foam stabilizer is calcium stearate, and the water meets the requirements for concrete mixing water.
[0077] A solid waste-based CO2 foam concrete and a preparation process thereof proposed in the present invention include the following steps:
[0078] (1) 25 parts of solid waste-based sulphoaluminate cement, 50 parts of hemihydrate gypsum, 5 parts of Portland cement, 20 parts of mineral powder and 2 parts of sodium bicarbonate are fully premixed and stirred for use;
[0079] (2) The raw material prepared in (1) is further mixed with 0.2 parts of retarder, 0.02 parts of water reducing agent, and 0.04 parts of calcium stearate, and the mixture is further mixed for 2 minutes to prepare a composite material for use;
[0080] (3) Take 30% tap water, add 3% potassium aluminum sulfate, and stir rapidly for 45 seconds to prepare a mixed solution for later use;
[0081] (4) Pour the mixed solution in (3) into the solution in (2) at once and stir rapidly for 150 seconds;
[0082] (5) The slurry mixed in (4) is poured into a mold, and allowed to stand for 1.5 days, demolded, and cured under standard curing conditions to obtain a lightweight and high-strength carbon dioxide foam concrete material.
[0083] Table 3 Performance of carbon dioxide foam concrete in implementation case 3
[0084]
[0085] Comparative Example 1
[0086] The difference from Example 1 is that ordinary sulphoaluminate cement is used instead of solid waste-based sulphoaluminate cement.
[0087] Comparative Example 2
[0088] The difference from Example 1 is that no solid waste-based sulphoaluminate cement is added, and the amount of silicate cement is adjusted to 30 parts.
[0089] Comparative Example 3
[0090] The difference from Example 1 is that no silicate cement is added, and the amount of solid waste-based sulphoaluminate cement is adjusted to 30 parts.
[0091] Comparative Example 4
[0092] The difference from Example 1 is that no hemihydrate gypsum is added, and the amount of solid waste-based sulphoaluminate cement is adjusted to 70 parts.
[0093] Comparative Example 5
[0094] The difference from Example 1 is that no mineral powder is added.
[0095] Table 4 Performance of carbon dioxide foamed concrete of Example 1 and Comparative Examples 1-5
[0096]
[0097] As can be seen from Table 4, the effects of the solid waste-based sulfoaluminate cement and ordinary sulfoaluminate cement used in the present invention are similar, and the cost is lower and the economy is better. Comparison of Example 1 with Comparative Examples 2 and 3 shows that, compared with only adding solid waste-based sulfoaluminate cement and silicate cement, the combination of the two can better improve the dry density and compressive strength of concrete. Comparison of Example 1 with Comparative Example 4 shows that, compared with only adding solid waste-based sulfoaluminate cement, the addition of hemihydrate gypsum can better improve the performance of concrete and stabilize the foam state. Comparison of Example 1 with Comparative Example 5 shows that the addition of mineral powder effectively improves the dry density and compressive strength of concrete.
[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A CO2 foam concrete material based on a solid waste-based multi-component gelling system, characterized in that: The invention is composed of the following components in percentage by mass: 20%-42% of solid waste-based sulphoaluminate cement, 15%-60% of hemihydrate gypsum, 6%-15% of Portland cement, 0-20% of mineral powder, 2%-4% of sodium bicarbonate, 3%-6% of potassium aluminum sulfate, 0.2%-0.4% of retarder, 0.02%-0.2% of water reducer and 0.02%-0.06% of calcium stearate, and the sum of the percentages of each raw material is 100%.
2. The CO2 foam concrete material based on a solid waste-based multi-component gelling system according to claim 1, characterized in that: The preparation method of the solid waste-based sulphoaluminate cement comprises: drying and mixing 80-90 parts of sulphoaluminate cement clinker, 15-20 parts of desulfurized gypsum and 5-10 parts of stone powder; adding the mixed raw materials into a kiln and calcining them at a temperature of 1250-1300° C. for 30-40 minutes to prepare the solid waste-based sulphoaluminate cement.
3. The CO2 foam concrete material based on solid waste-based multi-component gelling system according to claim 1, characterized in that: The retarder is at least one of boric acid and tartaric acid.
4. The CO2 foam concrete material based on solid waste-based multi-component gelling system according to claim 1, characterized in that: The water reducer is at least one of a polycarboxylate water reducer and a naphthalene water reducer.
5. The CO2 foam concrete material based on solid waste-based multi-component gelling system according to claim 1, characterized in that: Water-cement ratio 0.3-0.
45.
6. A method for preparing a CO2 foam concrete material based on a solid waste-based multi-component gelling system, characterized in that: include: The solid waste-based sulphoaluminate cement, hemihydrate gypsum, silicate cement, mineral powder and sodium bicarbonate are uniformly mixed to obtain a premix; Adding a retarder, a water reducing agent and calcium stearate to the premix, and mixing them evenly to obtain a composite material; Prepare potassium aluminum sulfate solution; Adding the potassium aluminum sulfate solution to the composite material, mixing evenly, to obtain a slurry; The slurry is poured into a mold, allowed to grow and form, demoulded, and cured to obtain the product.
7. The method for preparing a CO2 foam concrete material based on a solid waste-based multi-component gelling system according to claim 6, characterized in that: Add retarder, water reducer and calcium stearate to the premix and mix for 2-5 minutes.
8. The method for preparing CO2 foam concrete material based on solid waste-based multi-component gelling system according to claim 6, characterized in that: In the potassium aluminum sulfate solution, the mass ratio of potassium aluminum sulfate to water is 3-6:30-45.
9. The method for preparing a CO2 foam concrete material based on a solid waste-based multi-component gelling system according to claim 6, characterized in that: The potassium aluminum sulfate solution is added to the composite material and mixed for 120-180 seconds.
10. Application of the CO2 foam concrete material based on a solid waste-based multi-component gelling system as claimed in any one of claims 1 to 5 in the fields of construction and road construction.
Citation Information
Patent Citations
Sulfoaluminate cement foam concrete taking carbon dioxide as foaming gas and preparation method thereof
CN107089838A
Cited By
Lightweight foamed building material and preparation method thereof
CN120025133A
O2-CO2 composite chemical foaming-based high-performance solid waste-based foam concrete as well as preparation method and application thereof
CN120058330A
A high-performance solid waste-based foamed concrete based on O2-CO2 composite chemical foaming, and its preparation method and application
CN120058330B